Quality of Life of Children from Families Affected by Migration: The Role of Educational Policies - Aniela Matei; Mihaela Ghența (MDPI AG, 2024)
The problems of children from Romanian transnational families represent a current issue and one of great interest in the field of public policies that need to be developed in Romania in order to offer solutions that will lead to an increase in the quality of life within these families. This article reflects, based on the results of a survey among parents/grandparents who care for children from transnational families and two focus groups with authorities/organizations with a role in managing the problems of transnational families, the main issues faced by children from these families within education. The results obtained indicate an increased need for intervention in the following areas: support to avoid school dropout; education regarding the negative effects of drug, alcohol and other toxic substance consumption; and supervision in the completion of school assignments. All these problems influence the educational course of children and consequently the quality of life of all family members. This article offers support to decision makers in the field of educational policies to effectively manage the real problems of these families, highlighting the vital role of substantiating public policies based on scientific studies.